2007
DOI: 10.1371/journal.pone.0001308
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Escherichia coli Nissle 1917 Inhibits Leaky Gut by Enhancing Mucosal Integrity

Abstract: BackgroundProbiotics are proposed to positively modulate the intestinal epithelial barrier formed by intestinal epithelial cells (IECs) and intercellular junctions. Disruption of this border alters paracellular permeability and is a key mechanism for the development of enteric infections and inflammatory bowel diseases (IBDs).Methodology and Principal FindingsTo study the in vivo effect of probiotic Escherichia coli Nissle 1917 (EcN) on the stabilization of the intestinal barrier under healthy conditions, germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
309
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(333 citation statements)
references
References 55 publications
14
309
2
8
Order By: Relevance
“…These results are in accordance with previous findings that the colonization of GF mice with probiotic bacteria induces the activation of IgA production and that a mixture of probiotic strains is more effective in the development of plasmablasts in the gut compared with single strains. 48 The intestinal barrier is immature in GF mice, 49 and Lmix significantly improves this condition. We found that the enterocyte brush borders of the GF mice were irregularly arranged and exhibited a decreased number of cytoskeletal microfilaments and a lack of elongation into the terminal web.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with previous findings that the colonization of GF mice with probiotic bacteria induces the activation of IgA production and that a mixture of probiotic strains is more effective in the development of plasmablasts in the gut compared with single strains. 48 The intestinal barrier is immature in GF mice, 49 and Lmix significantly improves this condition. We found that the enterocyte brush borders of the GF mice were irregularly arranged and exhibited a decreased number of cytoskeletal microfilaments and a lack of elongation into the terminal web.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] It has also been shown that treatment with these probiotics can enhance mucus production and consequently improve the physical barrier protecting the epithelial layer. 34,35 Products of bacterial fermentation can also play an important role in maintaining the intestinal barrier. It has been shown that short-chain fatty acids can act as trophic factors for mucosal and epithelial layers.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%
“…The probiotic, Escherichia coli Nissle 1917, mediates up regulation of tight junction protein, ZO-1 and prevents gut barrier disruption induced by sodium dextran sulfate-induced colitis [19] . In a recent study we evaluated the effect of LGG and proteins secreted by LGG (p75 and p40) on hydrogen peroxide-induced disruption of tight junctions in Caco-2 cell monolayers, a cell culture model of the intestinal epithelium [20] .…”
Section: Approach and Resultsmentioning
confidence: 99%